Polymer Nanoparticles Advancements for Gynecological Cancers - Lin X; Li Z; Huang Y; Li Y; Li Y; Zhang L; Wu M (International Journal of Nanomedicine)
Xiaorui Lin,1,2 Zihan Li,1,2 Yibao Huang,1,2 Yinuo Li,1,2 Yuting Li,1,2 Ling Zhang,1,2 Mingfu Wu1,2 1National Clinical Research Center for Obstetrical and Gynecological Diseases, Department of Gynecology, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430030, People’s Republic of China; 2Key Laboratory of Cancer Invasion and Metastasis, Ministry of Education, Wuhan 430030, People’s Republic of ChinaCorrespondence: Mingfu Wu, Email mingfuwutj@163.comAbstract: Gynecological cancers represent one of the leading causes of death in women and pose a critical global health challenge. While surgery and chemotherapy remain the first-line therapies for gynecological cancers, the persistently high morbidity and mortality rates have driven the urgent exploration of novel theranostic strategies. In recent years, polymer nanoparticles (PNPs) have gained increasing attention in the diagnosis and treatment of cancer due to their superior targeting ability and delivery efficiency. This review provides an overview of PNPs and their role in tumor diagnosis and treatment, with a strategic focus on their utility in gynecological cancers. It covers drug delivery, imaging, combination therapy, and theranostic integration in gynecological cancers, and summarizes the composition, principles and characteristics of diverse polymers and their cargoes. Furthermore, this work highlights innovative applications of PNPs in gynecological cancers management, spanning chemotherapy, immunotherapy, PARPi therapy, phototherapy and other therapies. Despite promising preclinical advancements in PNPs, formidable challenges persist in their clinical translation. This review serves as a comprehensive resource for researchers and clinicians aiming to optimize gynecological cancers theranostics as well as accelerate the development and clinical translation of PNPs.Keywords: polymer nanoparticles, gynecological cancer, theranostics, nanoparticles, ovarian cancer, cervical cancer, endometrial cancer, nanomedicine